2021
DOI: 10.1200/jco.20.01200
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in BRCA1/2 and Other Panel Genes in Patients With Metastatic Breast Cancer —Association With Patient and Disease Characteristics and Effect on Prognosis

Abstract: PURPOSE Among patients with metastatic breast cancer (mBC), the frequency of germline mutations in cancer susceptibility genes and the clinical relevance of these mutations are unclear. In this study, a prospective cohort of patients with mBC was used to determine mutation rates for breast cancer (BC) predisposition genes, to evaluate the clinical characteristics of patients with mutations, and to assess the influence of mutations on patient outcome. PATIENTS AND METHODS Germline DNA from 2,595 patients with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
45
4
17

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 49 publications
7
45
4
17
Order By: Relevance
“…The authors found that BRCA1/2 pathogenic variants were not associated with worse OS and identified an inverse association between ER expression and OS in those with BRCA1 mutations but not with BRCA2 pathogenic variants. 38 In the advanced scenario, a comprehensive publication was recently done by Fasching et al, 39 placebo groups, respectively [HR, 0.3, 0.15 to 0.61]). This led the authors to conclude that BRCA1/2 alterations might be considered a predictive biomarker of greater benefit from ribociclib.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that BRCA1/2 pathogenic variants were not associated with worse OS and identified an inverse association between ER expression and OS in those with BRCA1 mutations but not with BRCA2 pathogenic variants. 38 In the advanced scenario, a comprehensive publication was recently done by Fasching et al, 39 placebo groups, respectively [HR, 0.3, 0.15 to 0.61]). This led the authors to conclude that BRCA1/2 alterations might be considered a predictive biomarker of greater benefit from ribociclib.…”
Section: Discussionmentioning
confidence: 99%
“…Developed on the basis of germline BRCA1/2 mutations and their role in tumor pathology, poly (ADP-ribose) polymerase (PARP) inhibitors are a further therapy option for patients with advanced HER2-negative disease, including both triple-negative and hormone-receptor-positive BC patients, who make up about 50% of all aBC patients [ 95 ]. The OlympiAD trial for olaparib [ 96 ] and the EMBRACA trial for talazoparib [ 97 ] showed an improvement concerning PFS over a chemotherapy of physicians’ choice.…”
Section: Modern Approaches In Advanced Breast Cancermentioning
confidence: 99%
“…The SG-EBC Expert Panel did not advocate general testing of all breast cancer patients, despite the fact that almost a quarter of the experts were in favour of either offering panel testing to all breast cancer patients under 65 years of age or to all breast cancer patients regardless of age (Supplementary Table S1 , question 1). Recent research suggests that approximately 5 – 10% of all breast cancer cases involve a mutation in one of the known risk genes 1 , 2 , 3 , 4 , 5 .…”
Section: Breast Cancer Risk and Geneticsmentioning
confidence: 99%
“…Aktuelle Arbeiten gehen davon aus, dass bei ca. 5 – 10% aller Brustkrebspatientinnen eine Mutation in einem der bekannten Risikogene gefunden werden kann 1 , 2 , 3 , 4 , 5 .…”
Section: Brustkrebsrisiko Und Genetikunclassified